A ubiquitous protein is the source of naturally occurring peptides that are recognized by a CD8+ T-cell clone. - Udaka, K (1993)
We previously isolated from mouse spleen an octapeptide (LSPFPFDL) that in association with the class I major histocompatibility complex protein Ld is recognized by the antigen-specific receptor of an alloreactive CD8+ T-cell clone (2C). Guided by an assay dependent upon the same 2C T-cell receptor, we have now isolated from the same source another naturally occurring peptide. The second peptide (VAITRIEQLSPFPFDL) includes the entire octapeptide sequence and preliminary evidence suggests that it may be a natural precursor of the octapeptide. On finding extensive sequence homology between the 16-mer and part of human 2-oxoglutarate dehydrogenase, we determined the cDNA sequence of mouse 2-oxoglutarate dehydrogenase and found that the deduced amino acid sequence matches precisely the two naturally occurring peptides, indicating their origin by cellular processing of this ubiquitous self protein.